3D-Printed Collagen-Based Waveform Microfibrous Scaffold for Periodontal Ligament Reconstruction - Hsu-Hsiang Lin (International Journal of Molecular Sciences, 2021)
Reconstruction of the periodontal ligament (PDL) to fulfill functional requirement remains a challenge. This study sought to develop a biomimetic microfibrous system capable of withstanding the functional load to assist PDL regeneration. Collagen-based straight and waveform microfibers to guide PDL cell growth were prepared using an extrusion-based bioprinter, and a laminar flow-based bioreactor was used to generate fluidic shear stress. PDL cells were seeded on the respective microfibers with 0 or 6 dynes/cm2 fluidic shear stress for 1–4 h. The viability, morphology, adhesion pattern, and gene expression levels of PDL cells were assessed. The results revealed that upon bioprinting optimization, collagen-based microfibers were successfully fabricated. The straight microfibers were 189.9 ± 11.44 μm wide and the waveform microfibers were 235.9 ± 11.22 μm wide. Under 6 dynes/cm2 shear stress, PDL cells were successfully seeded, and cytoskeleton expansion, adhesion, and viability were greater. Cyclin D, E-cadherin, and periostin were upregulated on the waveform microfibers. In conclusion, 3D-printed collagen-based waveform microfibers preserved PDL cell viability and exhibited an enhanced tendency to promote healing and regeneration under shear stress. This approach is promising for the development of a guiding scaffold for PDL regeneration.